Implementasi Layanan Drive Thru dan Delivery Order Buku di Masa Pandemi Covid-19 pada Minat Baca Peserta Didik SDN Gajasari - Aning Risti Mahardita; Elsa Putri Ermisah Syafril (UM Purwokerto Press, 2022)
The Covid-19 pandemic condition has forced the world of education to prepare appropriate and good steps to maintain the quality of literacy, especially reading interest in Gajasari Elementary School students. The drive thru service and book delivery orders during the pandemic are innovations in the management of the book-borrowing process in accordance with the COVID-19 pandemic conditions. Therefore, this study aims to: (1) explain the process of borrowing and returning books during the covid-19 pandemic; (2) explain the implementation of drive thru services and book delivery orders during the pandemic on the reading interest of students at SDN Gajasari; (3) identify the supporting and inhibiting factors for implementing drive thru services and book delivery orders during the pandemic on the reading interest of students at SDN Gajasari. This research uses a qualitative design with a case study approach. Sources of data from all students, teachers, and parents of students at SDN Gajasari, Nglipar, Gunungkidul. Data collection techniques are in the form of participatory observation and observation through the library slims application, observation through communication on WhatsApp, interviews, and documentation from February to April 2020. Then, the data is displayed to get conclusions. The results of this study, are: (1) The process of borrowing books back during the covid-19 pandemic there was a decrease in visitors to library members by 74.19%. (2) The implementation of drive thru services and book delivery orders during the pandemic on the reading interest of students at SDN Gajasari increased by 238,4%. (3) The process of innovating drive thru services and delivery of book orders during the pandemic on students' reading interest experienced obstacles in the socialization of the program. Support for the implementation of service management is provided by all teachers, employees, parents of students, committees, and DISPUSIP Gunungkidul Regency.